THE DIFFERENCES OF CORRELATION OF THE TIMI, GRACE, AND KILLIP RISK SCORES AS PREDICTOR PROGNOSIS PATIENTS WITH NON ST-ELEVATION MYOCARD INFARCTION ACUTE CORONARY SYNDROME IN ICCU RSUD DR.ISKAK TULUNGAGUNG - Rina Anggraini; Titin Andri Wihastuti; Dewi Kartikawatiningsih (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Acute Coronary Syndromes is the leading cause of short-term and long –term mortality. An aggressive treatment approach has the potential to change the prognosis of patients with ACS, although its depends on risk factors. There are several risk scores such as Thrombholysis in Myocardial Infarction (TIMI), Global Registry of Acute Coronary Events (GRACE), and Killip. The aim of this study is to analyse the differences of correlation of TIMI, GRACE, and Killip risk scores as predictor Length Of Stay patients with Non St-Elevation Myocard Infarction ACS. The method of this study utilized an analytic observational design with the cohort retrospective. The research was conducted at RSUD Dr.Iskak Tulungagung used 98 samples of medical records patient with NSTEMI ACS in the past 8 months (January-August 2017). The data collection techniques was completing risk score of TIMI, GRACE, and Killip and Length of Stay patient in ICCU ward. The results and analyse of Spearman Rank showed that TIMI has p = 0,000 r = 0.466, GRACE p = 0,000 r = 0.598, and Killip p = 0,000 r = 0.441 (p < 0,05), so that it can be said that there was significant differences between the risk score of TIMI, GRACE and Killip as predictor prognosis patient with NSTEMI ACS. It can be concluded that the TIMI, GRACE and Killip risk scores have correlation as predictor prognosis patient with NSTEMI ACS, which is GRACE risk score has superior to TIMI and Killip.